ESTUDIO DE FACTIBILIDAD TÉCNICO-ECONÓMICA DE ESTACIONES DE CARGA RÁPIDA PARA DISPOSITIVOS MÓVILES EN FORMA INALÁMBRICA - CARDENAS MUÑOZ , LUIS ALONSO (2025)
This study aims to assess the technical and economic feasibility of implementing fast-charging stations for mobile devices using wireless technology